3,4,5-Trichloroaniline Nephrotoxicity in Vitro: Potential Role of Free Radicals and Renal Biotransformation - Racine, Christopher (Int J Mol Sci, 2014)
Chloroanilines are widely used in the manufacture of drugs, pesticides and industrial intermediates. Among the trichloroanilines, 3,4,5-trichloroaniline (TCA) is the most potent nephrotoxicant in vivo. The purpose of this study was to examine the nephrotoxic potential of TCA in vitro and to determine if renal biotransformation and/or free radicals contributed to TCA cytotoxicity using isolated renal cortical cells (IRCC) from male Fischer 344 rats as the animal model. IRCC (~4 million cells/mL; 3 mL) were incubated with TCA (0, 0.1, 0.25, 0.5 or 1.0 mM) for 60–120 min. In some experiments, IRCC were pretreated with an antioxidant or a cytochrome P450 (CYP), flavin monooxygenase (FMO), cyclooxygenase or peroxidase inhibitor prior to incubation with dimethyl sulfoxide (control) or TCA (0.5 mM) for 120 min. At 60 min, TCA did not induce cytotoxicity, but induced cytotoxicity as early as 90 min with 0.5 mM or higher TCA and at 120 min with 0.1 mM or higher TCA, as evidenced by increased lactate dehydrogenase (LDH) release. Pretreatment with the CYP inhibitor piperonyl butoxide, the cyclooxygenase inhibitor indomethacin or the peroxidase inhibitor mercaptosuccinate attenuated TCA cytotoxicity, while pretreatment with FMO inhibitors or the CYP inhibitor metyrapone had no effect on TCA nephrotoxicity. Pretreatment with an antioxidant (α-tocopherol, glutathione, ascorbate or N-acetyl-l-cysteine) also reduced or completely blocked TCA cytotoxicity. These results indicate that TCA is directly nephrotoxic to IRCC in a time and concentration dependent manner. Bioactivation of TCA to toxic metabolites by CYP, cyclooxygenase and/or peroxidase contributes to the mechanism of TCA nephrotoxicity. Lastly, free radicals play a role in TCA cytotoxicity, although the exact nature of the origin of these radicals remains to be determined.